THE EFFECT OF ANTIOXIDANT ON ORGANOLEPTIC, BIOCHEMICAL, AND MICROBIOLOGICAL PARAMETERS OF ICE CREAM - OSYPENKOVA, IRYNA; CHEPURNA, OKSANA; KURYLENKO, YULIIA; HORBUNOVA, ADELINA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Abstract. Ice cream is a unique product, which is in great demand among the population. Its quality is formed under the influence of chemical composition and technological process during the production of the final product. Biochemical and microbiological processes play an important role in this process, influencing shelf life and organoleptic characteristics. The wide range of additives, flavourings, and aromas used in dairy production allows us to expand the range of ice cream products. In recent years, more and more attention has been paid to natural, plant-based ingredients that improve the consumer properties of products, as well as their biological and nutritional value. Particular attention is paid to natural additives that have antioxidant properties and no negative side effects on the human body. Ice cream is a polydisperse system containing about 20% milk fat, which has a special taste and high digestibility. During the mixing process, the product is saturated with oxygen from the air, which, if not handled properly during storage, can contribute to fat oxidation. This article examines the effect of red grape pomace powder on the quality of ice cream. The pomace contains resveratrol, which is a plant antibiotic - phytoalexin. In addition to its antibacterial properties, resveratrol has antioxidant activity. The antioxidant and antimicrobial properties of resveratrol and the organoleptic properties of the finished product were investigated. The results obtained prove the expediency of using a plant additive, which inhibits the oxidation processes and the development of microflora during storage. The use of red grape pomace powder can increase the stability of ice cream by 0.9 times in terms of peroxide number and by 0.7 times in terms of 2-TBA test. Microbiological indicators decreased by 42% within a month. The organoleptic characteristics depend on the quality of the product’s dairy raw materials and plant additives. Organoleptic control helps to identify defects in taste, smell, structure, texture, and colour in order to identify the causes of their occurrence in a timely manner. No significant deviations were detected in these samples, confirming their quality.